Assessing the Relevance of Framing Messages on Backing Intentions in Crowdfunding Social Cause-related Marketing Campaign (Journal of Social Sciences Review, 2022)
This study investigates the interaction effects of framing messages and social cause-related marketing on support intentions in crowdfunding campaign message narratives. Hypothesis were tested first by using 430 samples in an independent-samples t-test. The mean value difference demonstrates that the social cause-related marketing (SCRM) project (mean = 3.784) has a significantly bigger effect on backing intention than the non-SCRM project (mean = 3.012). This supports the study hypothesis that individuals involved in SCRM crowdfunding have a higher backing intention than those who are not involved.  The results further indicated significantly greater backing intentions with social cause-related marketing positive framing messages than negative attribute framing messages without cause-related marketing, whereas there was no significant difference between negative attribute framing messages with social cause-related marketing. This finding provides new insights for project initiators for using crowdfunding platforms for a social marketing campaign.
Keywords: Framing Messages; Backing Intentions; Crowdfunding; Marketing Campaign